An Evaluation of Liminality in Nadine Gordimer's July's People - KABAK, MURAT (My University, 2020)
Set during a civil war in the apartheid South Africa, Nadine Gordimer's July's People is centred around the relationship between the Smales family and their former servant July. As the communal ties disintegrate in the novel, three objects play a vital role in our understanding of the characters. For the purposes of this study, these symbols not only help us to reveal the nature of spatial-temporal dislocation but also reveal Gordimer's commentary on the apartheid South Africa. This study aims to contribute the existing scholarship by focusing on the liminal/in-between experience in July's People through analyzing the novel's preoccupation with subject-object relationship.
Keywords: Dislocation; July's People; Nadine Gordimer; spatiality; temporality; mekansallık; geçicilik